Quali Coffee Roastery: Asesmen Alienasi Budaya Organisasi Pemanggang Kopi Gelombang Ketiga berbasis Kapitalis/Laba - Buhaira Iza (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
The “assessment” & “alienation assessment” examination method, which analyzes how gift-exchange values shape the value of a commodity in the capitalist economic mode – focuses on analyzing “gift-giving” patterns that occur within the “supply chain” as well as the relationships between business owners, labor and commodity in the so-called “impersonal and capitalist mode”. Through ethnographic research on the third wave cultured coffee roasting business entity of "Quali Coffee Roastery", alienation and non-alienating values can also be analyzed in the capitalistic commodity production, distribution and supply chain of third wave coffee. Results from this article shows that a third wave coffee capitalist/profit-oriented organization is able to consciously determine which factors of production and distribution that can be alienated or non-alienated in its commodity production activities. Organizational culture & leadership concept presences are crucial in the deciding occurrence of alienation/non alienation pattern on one actor part of the capitalist-mode business supply chain.